Expert System For Diagnosing Helminthic Disease In Children Using The Bayes Probability Technique - Dedy Trisanto; Nofita Rismawati; Millati Izzatillah; Muhamad Femy Mulya (Journal of Information System, Informatics and Computing, 2022)
Worm disease or Ascariasis is an infection caused by the Ascaris lumbricoides worm that lives in the human body. Everyone is susceptible to this disease, but it is most common in children. Children who experience intestinal worms can be shown from a variety of symptoms from mild to those that interfere with the child's growth. This study aims to create a system that can adopt the knowledge of an expert who can provide users with diagnostic information such as from an expert regarding intestinal worms. The research uses the Bayesian Probability method. Bayes theorem is a method for generating parameter estimates by combining information from samples and other information that has been previously available. The expert system for diagnosing intestinal worms has been successfully implemented with a desktop-based application. The expert system can help the user get a diagnosis of the type of intestinal worms suffered according to the symptoms experienced.